Redefining the Framework of Teacher Competence in Islamic Educational Setting - Hasanah, Uswatun; Nafi'ah, Lulu Hidayatun (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2021)
The competence of teachers is a set of capabilities and knowledge that must be owned by teachers. The current problem occurring in Islamic educational institutions is that some of competencies possessed by these teachers are no longer becoming a concern and a reflection in carrying out their duties as teachers. This study aims to redefine the concept of teacher competence within the scope of Islamic education. This research is a library research using documentation data collection techniques, as well as Content Analysis techniques. Based on the results of the study, it is concluded that the four concepts of teacher competencies need to be redefined in developing Islamic religious into six competencies sequentially, namely spiritual competence, personality competence, pedagogic competence, professional competence, social competence and leadership competence. These sets of competence are very relevant to the teacher competence in the 21st century as a reference in developing the learning process in Islamic education nowadays and in the future.